S33 Risk factors for frequent exacerbations in a real-life adult population with severe refractory asthma. (12th November 2019) - Yang, JF; Busby, J; Heaney, LG; Pfeffer, PE; Jackson, DJ; Mansur, AH; Menzies-Gow, A; Siddiqui, S; Brightling, CE; Patel, M; Thomson, NC; Lee, WT; et al.
Abstract : Introduction: Severe exacerbations are an important cause of morbidity in asthma. Risk factors for exacerbations have been reported in selected asthma populations, but not in a large real-world severe asthma population. Maintenance oral corticosteroids (OCS) is used in severe asthma and can suppress inflammatory biomarkers associated with frequent exacerbations (FE). We identified risk factors for FE in a severe refractory asthma population and examined whether risk factors differ in those treated with and without maintenance OCS. Methods: Adults with well-characterised refractory asthma from specialised asthma centres were recruited to a UK Severe Asthma Registry (UKSAR). Demographic data, co-morbidities, clinical and inflammatory biomarkers were collected. We conducted univariate and multivariate logistic regression to identify risk factors for FE, defined as ≥3 exacerbations treated with high-dose systemic corticosteroids in the past year. Results: 1235 patients fulfilled ERS/ATS criteria for severe asthma on the UKSAR. In univariate analyses, patients who were ex-smokers (OR 1.6, p<0.003), had a history of gastro-oesophageal reflux disease (OR 1.48, p=0.019), had an ACQ-7 score 0.75 to 1.5 (OR 2.48, p=0.010) or >1.5 (OR 4.85, p<0.001) were more likely to have FEs. In multivariate analyses, ACQ-7 score 0.75–1.5 and >1.5 were independent risk factors for FE (OR 3.46, p=0.014 and OR 9.69, p<0.001 respectively). There was a strong association between smoking history and FE in the maintenance OCS group (OR 2.74, p=0.011), but not in the non-maintenance OCS group (OR 0.86, p=0.700). In patients not on maintenance OCS, a higher risk of FE was observed in those with blood eosinophil count >0.45 x10^9/L or exhaled nitric oxide >50ppb (OR 1.70 and OR 1.58 respectively), however this association was not statistically significant (p=0.073 and p=0.085 respectively). ACQ-7 score >1.5 remained an independent risk factor in both the maintenance OCS and non-maintenance OCS groups (OR 8.45, p=0.006 and OR 9.86, p<0.001 respectively). Conclusions: Several factors were associated with FE risk in a real-world severe asthma population. ACQ-7 score was the strongest independent risk factor. Risk factors differed for patients not on maintenance OCS, but ACQ-7 score of >1.5 was an independent risk factor for FE regardless of maintenance OCS status. On behalf of the UK Severe Asthma Registry.